VIBRATION ANALYSIS OF COUPLING BOLT FOR TRACK EXCAVATOR FRAME AND WALKING - WANG WenBing; REN JiaJun; LI AiFeng; GAO XinYu (Jixie qiangdu)
In order to study the vibration characteristics of the bolt structure of the excavator and the crawler frame, the WK-75 mechanical excavator was used as the research object, The RecerDyn multi-body dynamics simulation software was used to simulate the excavator movement process and extracted load spectrum, and Fourier transform of the load spectrum by MATLAB to obtain the load spectrum frequency. The natural frequency of the bolt structure is obtained by ANSYS Workbench finite element analysis software. The frequency of the load spectrum and the natural frequency are compared for the loosing condition of the bolt structure. It is of some reference value to the further study on the vibration characteristics of the connecting bolt of the excavator.